2019
DOI: 10.3847/1538-4357/ab44bf
|View full text |Cite
|
Sign up to set email alerts
|

Proper Motions of Stellar Streams Discovered in the Dark Energy Survey

Abstract: We cross-match high-precision astrometric data from Gaia DR2 with accurate multi-band photometry from the Dark Energy Survey (DES) DR1 to confidently measure proper motions for nine stellar streams in the DES footprint: Aliqa Uma, ATLAS, Chenab, Elqui, Indus, Jhelum, Phoenix, Tucana III, and Turranburra. We determine low-confidence proper motion measurements for four additional stellar streams: Ravi, Wambelong, Willka Yaku, and Turbio. We find evidence for a misalignment between stream tracks and the systemic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 99 publications
6
91
0
1
Order By: Relevance
“…This is 10× larger than conventionally assumed for the LMC. Recently, it was shown that such a high LMC mass will not perturb the MW's disk to levels inconsistent with observations [62] and is both supported by the timing argument [63] and needed to explain the kinematics of the Orphan Stream [64] (and likely many other stellar streams whose kinematics are now measured by Gaia [65]). Furthermore, such high infall mass prevents the LMC disk from being tidally truncated by the MW, explaining new results that the LMC's outer stellar disk extends to a radius approximately half its current separation to the MW (∼ 18.5 kpc; [66,67]).…”
Section: The Lmc: a Massive Satellite On First Infallmentioning
confidence: 94%
“…This is 10× larger than conventionally assumed for the LMC. Recently, it was shown that such a high LMC mass will not perturb the MW's disk to levels inconsistent with observations [62] and is both supported by the timing argument [63] and needed to explain the kinematics of the Orphan Stream [64] (and likely many other stellar streams whose kinematics are now measured by Gaia [65]). Furthermore, such high infall mass prevents the LMC disk from being tidally truncated by the MW, explaining new results that the LMC's outer stellar disk extends to a radius approximately half its current separation to the MW (∼ 18.5 kpc; [66,67]).…”
Section: The Lmc: a Massive Satellite On First Infallmentioning
confidence: 94%
“…The candidate PSF stars were taken to be this locus of objects from about ≈ 16, where the objects begin to saturate, down to ≈ 22, where the stellar locus merges with the locus of faint, small galaxies (the stars magnitudes are always relative to the exposure/band where the stars have been detected). The stellar density varies across the DES footprint; it tends to be higher in those exposures closer to the galactic plane and in the presence of stellar streams (see Shipp et al 2018 for more details).…”
Section: Selection Of Psf Starsmentioning
confidence: 99%
“…Clearly the density perturbations induced by the LMC are complex -the Milky Way's dark matter halo shape is not accurately described as a spherical, oblate, prolate, or triaxial halo. It was recently shown that perturbations from a massive (∼ 10 11 ) LMC are required to match proper motion data from Gaia in simulations of the Orphan stellar stream (Erkal et al 2019;Shipp et al 2019). However, missing in such stream models is the response of the Milky Way's halo to the presence of the LMC (halo wakes) and the distortions to the LMC's dark matter distribution caused by the tidal field of the Milky Way.…”
Section: Quantifying the Shape Of The Milky Way's Dark Matter Halo Inmentioning
confidence: 99%